Ergonomics interventions improve quality in manufacturing: A case study - (:unkn) unknown (Inderscience Publishers, 2008)
Ergonomics interventions that enhance employee performance lead to better quality in manufacturing. This study exemplified Quality Improvement Through Ergonomics (QUITE) interventions in apparel manufacturing context. The study was conducted at two machine sewing lines in an apparel manufacturing company. Ergonomics problems and quality performance were assessed before and after interventions. Major ergonomics problems were awkward postures, musculoskeletal discomfort and difficulty in monitoring operation of machine needle and flow of stitches. Operators were given ergonomics training and a manual about correct work methods. A reminder figure showing correct work postures was installed on workstations. Workstation adjustments and machine tilting were applied. After interventions, significant reductions in ergonomics problems were attained, proportion of Sewing Operator Related Defective Products (SORDP) was reduced by 56% in Line 1 and by 52% in Line 2. It was concluded that ergonomics interventions served to improve quality via reduction of operator errors in machine sewing task. Copyright © 2008, Inderscience Publishers.
Keywords: Apparel manufacturing; Ergonomics; Ergonomics intervention; Machine sewing; Manufacturing; QEC; Quality improvement; Quick exposure check